The Mechanical Strength of a Mechanical Bond: Sonochemical Polymer Mechanochemistry of Poly(catenane) Copolymers. (6th October 2016) - Lee, Bobin; Niu, Zhenbin; Craig, Stephen L.
Abstract: Topological molecular connections and structures, including physical entanglements in polymer networks, knots along polymer chains, and rotaxanes in sliding ring gels, have important consequences for the physical properties of polymeric materials. Often these topologies contribute through their ability to bear mechanical stress, but experimental measures of their relative mechanical strength are rare. Here, we use sonochemical polymer mechanochemistry to assess the relative mechanical strength of a multicatenane copolymer relative to copolymers of cyclic and linear analogs. The relative mechanical strengths are obtained by comparing the limiting molecular weights ( M lim ) and contour lengths ( L lim ) of the polymers under pulsed ultrasound of their dilute solutions. The values of M lim and L lim, and thus the inferred mechanical strengths of the polymers, are effectively identical. The mechanical bonds of the catenanes are therefore as strong, or stronger, mechanically as the covalent bonds along the polymer backbone.